On self-knowledge - "Krishnamurti, J." (Chennai, 2010)
On Self-Knowledge is the first volume in a series titled 'Selections from the Decades'. The series aims at presenting a representative sample of talks that Krishnamurti gave between the 1940s and the 1980s. The book begins with the year 1947, a year that marked a milestone both in India's destiny and in the unfoldment of Krishnamurti's teachings. The concerns of that period had, understandably, to do with the political and social problems of the day. What is striking about Krishnamurti's approach, however, is that even while addressing contemporary issues, his answers are rooted in a timeless vision of life and truth. As such, he insists that a regeneration in society can come about only through a radical revolution in the consiciousness of the individual. And such a change, he avers, is possible only through self-knowledge. The talks in this book reveal how Krishnamurti takes us, step by step, on the journey of discovering ourselves.
Keywords: Self-Knowledge